1985
DOI: 10.1002/dc.2840010405
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural studies of malignant cells in fluids

Abstract: An ultrastructural study was performed on 104 sequential fluids in which more than eight malignant cells per ten high-power fields were found by routine light microscopy. The study included fluids associated with mesotheliomas, melanomas, lymphomas, squamous-cell carcinomas, small-cell anaplastic (oat-cell) carcinomas, and adenocarcinomas. Electron microscopic examination reliably separated lymphoid from epithelial malignancies and benign from reactive and malignant mesothelial cell proliferations. It also sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Various methods are described in the literature to improve the cytological diagnosis, including ÔThick and Thin smearsÕ, 6,7 improved preparation of the cell block, 2,8 compact cell blocks 9 and better fixation (CytoRich Red System, Thermo Electrone Corporation, Pittsburgh, PA, USA). 10 Flow cytometric analysis, 11 ultrastructural studies 12 and cytogenetics analysis 13 are also reported as useful adjuncts to cytopathological diagnosis. However, compared with all of these techniques our technique is very simple; no additional fixative or equipment is required.…”
Section: Discussionmentioning
confidence: 99%
“…Various methods are described in the literature to improve the cytological diagnosis, including ÔThick and Thin smearsÕ, 6,7 improved preparation of the cell block, 2,8 compact cell blocks 9 and better fixation (CytoRich Red System, Thermo Electrone Corporation, Pittsburgh, PA, USA). 10 Flow cytometric analysis, 11 ultrastructural studies 12 and cytogenetics analysis 13 are also reported as useful adjuncts to cytopathological diagnosis. However, compared with all of these techniques our technique is very simple; no additional fixative or equipment is required.…”
Section: Discussionmentioning
confidence: 99%
“…These borderline cases can occupy an inordinate amount of time in routine diagnostic practice and account for a significant proportion of the literature as we attempt to develop reliable adjunctive studies to assist in these difficult cases. [1][2][3][4][5][6][7][8][9][10][11][12] The majority of these reports focus on the study of the abnormal cells in question, using a battery of special stains and techniques. In this article, we chose to study an associated third cell population by immunohistochemistry, in an attempt to confirm a previous observation (based on flow cytometry studies) that increased numbers of natural killer cells are associated with the presence of malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…In such morphologically equivocal cases, adjunctive studies useful in their evaluation, including histochemistry, immunohistochemical stains, and other techniques, have been attempted. [1][2][3][4][5][6][7][8][9][10][11][12] Recently, the use of flow cytometry in the identification of specific lymphocyte subpopulations associated with the presence of malignancy has been investigated. One study by Green and Griffin 13 suggested that an increased percentage of natural killer (NK) cells, as determined by flow cytometry, was significantly associated with the presence of metastatic carcinoma, suggesting its potential utility as an adjunct to microscopic examination.…”
mentioning
confidence: 99%
“…The needle is then removed and the sample gently expressed into the vial containing the EM fixative. This method prevents shearing of the cells and allows the particles to aggregate; they can then be embedded using forceps to obtain the small pieces that have settled at the bottom of the vial and the rest of the sample is gently spun and the pellet submitted for specimen preparation following the routine EM method [7,8]. In this manner our cell recovery has improved from 40-50% [4] to 60-70% of all cases exhibiting enough cells permitting a diagnosis to be made.…”
Section: Methodsmentioning
confidence: 97%
“…A few cubic centimeters of fluid can be utilized for routine EM preparation and a diagnosis can be obtained with the use of the electron microscope. Fluids with high cellularity are excellent samples for EM [7]. If the cellularity is limited and only a few tumor cells are present, an ultrastructural diagnosis can still be rendered in most cases, although it may require detailed and sometimes prolonged evaluation.…”
Section: Methodsmentioning
confidence: 99%